2007
DOI: 10.3113/fai.2007.0006
|View full text |Cite
|
Sign up to set email alerts
|

Operative Management of Ankle Fractures in Patients with Diabetes Mellitus

Abstract: Most patients with diabetes can undergo open reduction and internal fixation of acute ankle fractures without complications. Patients with absent pedal pulses or peripheral neuropathy are at increased risk for complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
80
2
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(88 citation statements)
references
References 12 publications
4
80
2
2
Order By: Relevance
“…Some authors reported patient age to be an independent predictor for surgical site infections [43,45,59]. Wukich et al [64] did not find this association in 1000 patients undergoing foot and ankle procedures, nor have other studies [17,23,32,36,38,49]. Consistent with the literature, age and hardware placement were infrequent indications for use of prophylactic postoperative oral antibiotics from our participants [13,17,23,32,36,38,49,64].…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Some authors reported patient age to be an independent predictor for surgical site infections [43,45,59]. Wukich et al [64] did not find this association in 1000 patients undergoing foot and ankle procedures, nor have other studies [17,23,32,36,38,49]. Consistent with the literature, age and hardware placement were infrequent indications for use of prophylactic postoperative oral antibiotics from our participants [13,17,23,32,36,38,49,64].…”
Section: Discussionsupporting
confidence: 80%
“…Peripheral neuropathy was the strongest predictor of infection [64]. Costigan et al [17] reported infection in 83% of patients with diabetes lacking preoperative pedal pulses and 92% with peripheral neuropathy after surgical treatment for ankle fractures. Numerous studies have supported associations with increased wound complications and surgical site infections in patients with complicated diabetes, peripheral vascular disease, and wound compromising medications [8,16,23,36,43,44,59].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Type I diabetes mellitus negatively alters the mechanical and biologic properties of bone [3,22] and has been associated with an increased risk of complications with fracture healing, including delayed union, wound necrosis, and increased incidence of infection [6,8,23,25,28]. An intervention that would overcome this inhibition of fracture healing would be useful clinically.…”
Section: Discussionmentioning
confidence: 99%
“…Type I diabetes mellitus is associated with an increased risk of complications with fractures, including delayed union, wound necrosis, and increased incidence of infection [6,8,23,25,28]. Many of these complications result from progressive small vessel arterial disease and peripheral neuropathy that develop with time and are largely untreatable [19,29].…”
Section: Introductionmentioning
confidence: 99%